PEMIKIRAN DALAM NOVEL SEMANIS KYUHO KARYA GHAZALI LATEH: THOUGHTS IN THE NOVEL ‘SEMANIS KYUHO’ BY GHAZALI LATEH - Hashim, Nurhamizah; Mat Hussain, Eizah; Razali, Asbah; Mat Madmin, Natasah (Jurnal Pengajian Melayu (JOMAS), 2020)
Thinking is the process of building knowledge and understanding that involves mental activity in the human brain. During the process of thinking, the human brain will attempt to understand external stimulation received through the senses, form concepts, make interpretations and react based on existing experiences in memory. The concept of thinking is very broad and can be explained using various approaches. Hence, this study examined the aspects of thinking in the teen novel ‘Semanis Kyuho’ by Ghazali Lateh (2016). The novel won the Utusan Group Literature Prize in 2015. The objectives of this study were to identify, analyse and formulate aspects of thinking found in the abovementioned youth novel. The approach utilised the general concept of thought and thinking in Malay literature as suggested by academics like Dewey (1910) from the West and Mohd Yusof Othman (1998), Zainal Kling (1993), Hashim Awang (1997) and several others from the East. The study also involved only literary research and text analysis. Findings show two dominant aspects of thinking within the novel, namely thinking from the aspect of socio-economic issues such as poverty and hardship faced by villagers and the aspect of socio-culture such as the societal emphasis on education to attain a brighter future. Keywords: Thought, Teen Novel, Semanis Kyuho, Socio-economics, Socio-Culture.